Fatigue limit and life evaluation formulae for compressive mean stress states. Issue 17 (22nd November 2018) - Cai, Xiaojing; Li, Xiangzhe; Xu, Jinquan
ABSTRACT: Considering the difference of stress concentration behaviour near micro-defects in materials, a unified fatigue limit evaluation formula has been developed, which can be applied to compressive mean stress states without the necessity of introducing additional material's properties except for the modification parameter of mean stress. A generalised life evaluation formula has also been proposed and the dependence of fatigue life on mean stress can be simply expressed by the effect of fatigue limit corresponding to the mean stress. By considering the effect of fatigue limit corresponding to the compressive mean stress, the fatigue life can be evaluated by the same generalised formula as that developed for tensile mean stress state, without the necessity of carrying out additional S–N curve fatigue tests.